2021
DOI: 10.1186/s13195-021-00921-5
|View full text |Cite
|
Sign up to set email alerts
|

The apolipoprotein receptor LRP3 compromises APP levels

Abstract: Background Members of the low-density lipoprotein (LDL) receptor family are involved in endocytosis and in transducing signals, but also in amyloid precursor protein (APP) processing and β-amyloid secretion. ApoER2/LRP8 is a member of this family with key roles in synaptic plasticity in the adult brain. ApoER2 is cleaved after the binding of its ligand, the reelin protein, generating an intracellular domain (ApoER2-ICD) that modulates reelin gene transcription itself. We have analyzed whether A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Of the up-regulated transcripts, 612 are augmented by both Apoer2-ICDs, 49 by Apoer2-ICD[+19], and 57 by Apoer2-ICD[Δ19]. One of the transcripts up-regulated by only the Apoer2-ICD[+19] is LRP3, whose expression is increased by Apoer2 and is reduced in the frontal cortex of postmortem AD brains [ 19 ]. The top functional enrichment categories for these up-regulated transcripts were post-synapse, cell junction organization, and cellular component morphogenesis (Figure S 5 A, Table S 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the up-regulated transcripts, 612 are augmented by both Apoer2-ICDs, 49 by Apoer2-ICD[+19], and 57 by Apoer2-ICD[Δ19]. One of the transcripts up-regulated by only the Apoer2-ICD[+19] is LRP3, whose expression is increased by Apoer2 and is reduced in the frontal cortex of postmortem AD brains [ 19 ]. The top functional enrichment categories for these up-regulated transcripts were post-synapse, cell junction organization, and cellular component morphogenesis (Figure S 5 A, Table S 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research had found that 200 μM of Al(mal) 3 -exposed PC12 cells after 12 h and 24 h resulted in a significant increase in the Aβ 42 protein content of PC12 cells and a significant decrease in the Aβ 40 protein content. Reelin and Dab1 expression levels also changed during Aβ metabolism (Cuchillo-Ibanez et al, 2021; Thordardottir et al, 2017). Reelin can inhibit the APP amyloid hydrolysis pathway; on the other hand, it can promote the interaction between Dab1 and APP, and inhibit the generation of toxic Aβ.…”
Section: Discussionmentioning
confidence: 99%
“…The first was LDL receptor related protein 8 ( LRP8 ), AS of which is associated with Braak stage in both regions. It is a member of the LDL receptor family and performs key functions in brain development by affecting synaptic plasticity, allowing lipoprotein trafficking, and promoting cell development [ 34 ]. Also, it is involved in APP processing and Aβ secretion, and hence plays a significant role in AD pathogenesis and neurodegeneration [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a member of the LDL receptor family and performs key functions in brain development by affecting synaptic plasticity, allowing lipoprotein trafficking, and promoting cell development [ 34 ]. Also, it is involved in APP processing and Aβ secretion, and hence plays a significant role in AD pathogenesis and neurodegeneration [ 34 ]. Notably, previous studies have demonstrated that LRP8 mRNA splicing alterations are correlated with AD progression through remodeling LRP8 functions [ 35 ].…”
Section: Discussionmentioning
confidence: 99%